2022
DOI: 10.1017/s0014479722000114
|View full text |Cite|
|
Sign up to set email alerts
|

Yield response of tef (Eragrostis tef) to nitrogen, phosphorus, potassium and sulphur under balanced fertilization on Vertisols in different agroecological zones of Ethiopia

Abstract: Summary Nutrient deficiency is a major constraint in tef (Eragrostis tef (Zucc.) Trotter) production in Ethiopia. In the past, a blanket recommendation of nitrogen (N) and phosphorus (P) fertilizers has been applied regardless of the diversity of agroecological zones and soil types. As crop responses declined with widespread deficiencies of nutrients, farmers have lost interest in applying the recommended fertilizer rates. The present study was conducted with the objective of quantifying the response of tef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
2
3
2
Order By: Relevance
“…Amare et al [ 35 ] provided supporting evidence that nitrogen fertilizer is the primary and most significant yield-limiting nutrient, followed by phosphorus, confirming the idea that the decline in soil fertility affects crop production. Likewise, Alemayehu et al [ 36 ] and Chala et al [ 7 ] reported similar findings in their studies. The omission of nitrogen (N) and phosphorus (P) had a highly significant impact on reducing both the grain yield and yield components of tef.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Amare et al [ 35 ] provided supporting evidence that nitrogen fertilizer is the primary and most significant yield-limiting nutrient, followed by phosphorus, confirming the idea that the decline in soil fertility affects crop production. Likewise, Alemayehu et al [ 36 ] and Chala et al [ 7 ] reported similar findings in their studies. The omission of nitrogen (N) and phosphorus (P) had a highly significant impact on reducing both the grain yield and yield components of tef.…”
Section: Resultssupporting
confidence: 74%
“…production. Likewise, Alemayehu et al [36] and Chala et al [7] reported similar findings in their studies. The omission of nitrogen (N) and phosphorus (P) had a highly significant impact on reducing both the grain yield and yield components of tef.…”
Section: Plos Onesupporting
confidence: 68%
See 1 more Smart Citation
“…The non-significant tef grain and biomass yield difference showed that the application of all nutrient types (K, S, Zn, and B) did not have a significant contribution to yield as compared to N and P nutrients. However, the result disagreed with Gessesew et al ( 2022) and Chala et al (2022), who described that applying higher rates of N, P, S, Zn, and B nutrients enhances crop yield. Only increasing the rate of All+K by 150% gave a higher biological yield than NP nutrients.…”
Section: Tef Yield Response To Applied Nutrient Typescontrasting
confidence: 67%
“…(2022) and Chala et al. (2022) who described that applying higher rates of N, P, S, Zn, and B nutrients enhances crop yield.Tef grain yields varied from site to site in each district. The biomass yield showed a similar trend to the applied nutrient types and rates.…”
Section: Discussionmentioning
confidence: 99%